The effects of two equal-volume training protocols upon strength, body composition and salivary hormones in male rugby union players - BT Crewther; TOL Heke; JWL Keogh (Termedia Publishing House, 2016)
This study examined the effects of two equal-volume resistance-training protocols upon strength, body composition and salivary hormones in male rugby union players. Using a crossover design, 24 male rugby players completed a 4-week full-body (FB) and split-body (SB) training protocol of equal volume during the competitive season. One repetition maximum (1RM) strength, body composition via skinfold measurements and salivary testosterone (T) and cortisol (C) concentrations were assessed pre and post training. The FB and SB protocols improved upper (7.3% and 7.4%) and lower body 1RM strength (7.4% and 5.4%), whilst reducing body fat (-0.9% and -0.4%) and fat mass (-5.7% and -2.1%), respectively (all p ≤ 0.021). The SB protocol elevated T (21%) and C (50%) concentrations with a higher T/C ratio (28%) after FB training (all p ≤ 0.039). The strength changes were similar, but the body composition and hormonal results differed by protocol. Slope testing on the individual responses identified positive associations (p ≤ 0.05) between T and C concentrations and absolute 1RM strength in stronger (squat 1RM = 150.5 kg), but not weaker (squat 1RM = 117.4 kg), men. A short window of training involving FB or SB protocols can improve strength and body composition in rugby players. The similar strength gains highlight training volume as a key adaptive stimulus, although the programme structure (i.e. FB or SB) did influence the body composition and hormonal outcomes. It also appears that 1RM strength is associated with individual hormonal changes and baseline strength.